If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -7 = -9 + x Combine like terms: -4 + -7 = -11 -11 = -9 + x Solving -11 = -9 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -11 + -1x = -9 + x + -1x Combine like terms: x + -1x = 0 -11 + -1x = -9 + 0 -11 + -1x = -9 Add '11' to each side of the equation. -11 + 11 + -1x = -9 + 11 Combine like terms: -11 + 11 = 0 0 + -1x = -9 + 11 -1x = -9 + 11 Combine like terms: -9 + 11 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| -3(x-4)=18 | | 2(5c-1)-1=6c+9 | | 8x+7-5x=-17 | | 6-6(18x-12)=4x | | x^2+25x-150=0 | | 4(2x-4)=9x | | (x-2)-(2-x)= | | 10-5= | | 40+3y-12=13y-14-3y | | -(3y-5)+11= | | (6m-1)2=10 | | 70-2(x+3)=3(x-2) | | 5=9y | | 12(2x-6)+37=3x | | -6(4d+8)= | | 12x-(3x-12)=5+8x | | 2x^3+54= | | -3(6n-4)+3n= | | (x-1.4)=36 | | 36(x-1.4)= | | 20m^2+43m+14= | | 11-45=5(x-3)-4 | | 17(5c-1)-14=83c+17 | | -19n+12=-15n-12 | | 42=-7y | | 11=u-7 | | 2.5h=80 | | 11-12b=3 | | 4u+8=5u+3 | | 2.5=80 | | 4x=3x-7 | | 3y-y=4-18 |